ChemInform Abstract: Physico‐Chemical Foundations Underpinning Microarray and Next Generation Sequencing Experiments. Issue 25 (3rd June 2013) - Harrison, Andrew; Binder, Hans; Buhot, Arnaud; Burden, Conrad J.; Carlon, Enrico; Gibas, Cynthia; Gamble, Lara J.; Halperin, Avraham; Hooyberghs, Jef; Kreil, David P.; et al., et al.
Abstract Review: 92 refs.